The Effects of Using Spin Wheel Media on Counting Ability of Tunagrahita Students - Machdarini, Machdarini; Hidayat, Luqman (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This study aims to determine the effect of spin wheel media on the counting ability of tunagrahita students in class IV at SLB Negeri 2 Yogyakarta. This study used the one-group pre-test-post-test research method. Data collection in this study used written tests, and data analysis methods used non-parametric statistical data analysis techniques with the Wilcoxon Signed Rank Test (Wilxocon marked rank test) with the help of SPSS version 20. The results of Z value = -2.236 with Asymp Sig were obtained from the analysis results obtained in this study. (2-tailed) 0.025, which is below 0.05. From these results, it can be interpreted that Ho is rejected and Ha is accepted at an initial significance of 5%. Therefore, the hypothesis in this study, "There is an effect of using rotating wheels on the numeracy skills of tunagrahita students in class IV at SLB Negeri 2 Yogyakarta" can be accepted as true. So, this study can be concluded that there is an effect of using spin wheel media on the counting ability of grade IV tunagrahita students at SLB Negeri 2 Yogyakarta.